Phenotypic heterogeneity in seven Italian cases of aceruloplasminemia. (June 2018) - Pelucchi, Sara; Mariani, Raffaella; Ravasi, Giulia; Pelloni, Irene; Marano, Massimo; Tremolizzo, Lucio; Alessio, Massimo; Piperno, Alberto
Abstract: Introduction: Aceruloplasminemia is an ultra-rare hereditary disorder characterized by iron-restricted microcytic anemia and tissue iron overload associated with diabetes, retinal and progressive neurological degeneration. We describe genotypes and phenotypes at diagnosis, and disease evolution of seven Italian patients. Methods: Anagraphical, biochemical, genetic, clinical and instrumental data were collected at diagnosis and during a long-term follow-up. Mutations, ferroxidase activity and Western Blot analysis of ceruloplasmin were performed according to standard protocols. Results: Three mutations were already described (p.Phe217Ser, deletions of exon 11 and 12), p.Ile991Thr is a very rare variant, p.Cys338Ser and IVS6+1G > A were novel mutations. In silico analyses suggested they were highly likely or likely to be damaging. At diagnosis, 100% had microcytosis, 86% had mild-moderate anemia, low serum iron and high serum ferritin. Four (57%) had type 1 diabetes or glucose intolerance, 3/7 had neurological manifestations, and only one had early diabetic retinopathy. All but one underwent iron chelation therapy requiring temporary discontinuation because of anemia worsening. At the end of follow-up, three patients aggravated and 2 developed neurological symptoms; only two patients were free of neurological manifestations and showed mild or absent brain iron. Conclusion: Aceruloplasminemia phenotypes ranged from classical characterized by progressive neurologic derangement to milder in which signs of systemic iron overload prevailed over brain iron accumulation. Within this large heterogeneity, microcytosis with or without anemia, low serum iron and high serum ferritin were the early hallmarks of the disease. Therapeutic approaches other than iron chelation should be explored to reduce morbidity and improve life expectancy. Highlights: In Italian ACP patients, retinopathy was not as common as previously reported. Iron chelation was unable to rescue or significantly prevent neurological impairment. Microcytosis was the hallmark of disease in all the patients. Ferroxidase activity could be a prognostic marker of the disease.